A refined protocol for calculating air flow rate of naturallyventilated broiler barns based on co2 mass balance (2014)
This study was conducted to evaluate relatively simple protocols for monitoring ventilation rate (VR) in naturally-ventilated barns (NVB). The test protocols were first applied to a mechanically-ventilated broiler barn (MVB), where VR was estimated more accurately and then were used to calculate VR in the NVB. CO2 concentrations were measured with two different sampling schemes: (S1) the average of indoor measurements along the length of the building at two heights of 0.5 m and 1.5 m from the litter floor; and (S2) same as previous but with concentration measurements taken only at 0.5 m from litter. The dynamic metabolic CO2 production rate of the birds was predicted with two different algorithms: (A1) remaining constant throughout the dark and light periods, and (A2) varying with animal activity on an hourly basis. The results demonstrated that the combination of S2 with A1 or A2 yielded the best estimate of building VR in the NVB.